2019
DOI: 10.1111/epi.14700
|View full text |Cite
|
Sign up to set email alerts
|

SCN1A/NaV1.1 channelopathies: Mechanisms in expression systems, animal models, and human iPSC models

Abstract: Summary Pathogenic SCN1A/NaV1.1 mutations cause well‐defined epilepsies, including genetic epilepsy with febrile seizures plus (GEFS+) and the severe epileptic encephalopathy Dravet syndrome. In addition, they cause a severe form of migraine with aura, familial hemiplegic migraine. Moreover, SCN1A/NaV1.1 variants have been inferred as risk factors in other types of epilepsy. We review here the advancements obtained studying pathologic mechanisms of SCN1A/NaV1.1 mutations with experimental systems. We present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 90 publications
4
38
0
Order By: Relevance
“…The present study did not evaluate the properties of the underlying sodium currents. However, studies in heterologous systems have shown that missense mutations located in transmembrane segments can lead to misfolding of the sodium channel assembly ( Rusconi et al, 2007 , 2009 ; Bechi et al, 2015 ; for review, see Terragni et al, 2018 ; Mantegazza and Broccoli, 2019 ). The Scn1a K1270T missense mutation, located in the S2 transmembrane segment of domain DIII, could lead to misfolding of the Nav1.1 channel in a way that alters voltage-dependent gating properties and/or trafficking of the channel, which in turn could contribute to the reduced AP amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…The present study did not evaluate the properties of the underlying sodium currents. However, studies in heterologous systems have shown that missense mutations located in transmembrane segments can lead to misfolding of the sodium channel assembly ( Rusconi et al, 2007 , 2009 ; Bechi et al, 2015 ; for review, see Terragni et al, 2018 ; Mantegazza and Broccoli, 2019 ). The Scn1a K1270T missense mutation, located in the S2 transmembrane segment of domain DIII, could lead to misfolding of the Nav1.1 channel in a way that alters voltage-dependent gating properties and/or trafficking of the channel, which in turn could contribute to the reduced AP amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…One of these mutations (NaV1.1) has also been identified in FHM-3 patients (Tiwari et al, 2020), although its role in migraines and CSD is less clear. In particular, it remains an open question whether the FHM-3 mutation leads to a gain or loss of function of the channel (Hedrich et al, 2014;Mantegazza & Broccoli, 2019). NaV1.1 channels are particularly important for interneuronal excitability, and it is also unclear how changes in this excitability may contribute to initiating CSD.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, mutations in the sodium channel prevalent in cortical interneurons have been implicated in the initiation of CSD. Specifically, a mutation of the NaV 1.1 sodium channel (SCN1A gene) has been identified as FHM-3 (Dichgans et al, 2005;Mantegazza & Broccoli, 2019;Tiwari et al, 2020). At this point, it is not clear whether this mutation causes a gain or loss of function in the channel (Cestèle et al, 2008(Cestèle et al, , 2013Kahlig et al, 2008;Mantegazza & Broccoli, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations